The use of self-report measures to examine changes in perception in response to fittings using different signal processing parameters. - Anderson, Melinda; Rallapalli, Varsha; Schoof, Tim; Souza, Pamela; Arehart, Kathryn (International Journal of Audiology, 2018)
Clinicians have long used self-report methods to assess hearing aid benefit. However, there are fewer data as to whether self-report instruments can be used to compare differences between signal processing settings. This study examined how self-perceived performance varied as a function of modifications in signal processing using two self-report measures. Data were collected as part of a double-blind randomised crossover clinical trial. Participants were fit with two fittings: mild processing (slow time constants, disabled frequency lowering) and strong processing (fast time constants, frequency lowering enabled). The speech, spatial, and qualities of hearing (SSQ) questionnaire and the Effectiveness of Auditory Rehabilitation (EAR) questionnaire were collected at multiple time points. Older adults with sensorineural hearing loss who had not used hearing aids within the previous year participated (49 older adults were consented; 40 were included in the final data analyses). Findings show that listeners report a difference in perceived performance when hearing aid features are modified. Both self-report measures were able to capture this change in perceived performance. Self-report measures provide a tool for capturing changes in perceived performance when hearing aid processing features are modified and may enhance provision of an evidence-based hearing aid fitting.